Dominant protozoan species in rhizosphere soil over growth of Beta vulgaris L. in Northeast China. Issue 1 (1st January 2020) - Zheng, Wei-Bin; Wang, Li; Wang, Xiang; Du, Ming-Lei; Ge, Chang; Wang, Qiu-Hong; Zhang, Mei-Yu; Yang, Man-Li; Zheng, Xiao-Dan; Chen, Ying; Lee, Duu-Jong
ABSTRACT: This paper identified the dominant protozoan species in the four layers of rhizosphere soil during the six growth stages of Beta vulgaris L . and analyzed the correlations of the abundance and diversity of the dominant protozoan species with soil properties at different growth stages and soil depth. A total of 15 species of protozoa were identified; among them, Colpoda sp., Bodo sp., two kinds of Oxytricha sp., and Tachysoma sp. were the most dominant species of Beta vulgaris L . rhizosphere soil. The Colpoda sp. was eurytopic species in the Beta vulgaris L . rhizosphere soil and Tachysoma sp., Vorticella sp., Colpoda sp., Oxytricha sp.1, and Oxytricha sp. 2 were noted closely related to the acceleration function of circulation of N and P elements in soils. These dominant protozoan species were proposed to play a significant role of fertilization on N supply in rhizosphere soil during the initial growth of Beta vulgaris L .